1996
DOI: 10.1128/aem.62.2.450-455.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperature on starvation-survival of the eel pathogen Vibrio vulnificus biotype 2

Abstract: At present, no reports exist on the isolation of the eel pathogen Vibrio vulnificus biotype 2 from water samples. Nevertheless, it has recently been demonstrated that this biotype can use water as a route of infection. In the present study, the survival of this pathogen in artificial seawater (ASW) microcosms at different temperatures (25 and 5؇C) was investigated during a 50-day period, with biotype 1 as a control. V. vulnificus biotype 2 was able to survive in the culturable state in ASW at 25؇C in the free-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 34 publications
4
44
1
Order By: Relevance
“…After 10 days in the nonculturable state (22 days after commencement of the experiment), no cells were recovered after resuscitation on the amended plates (data not shown). A similar phenomenon has been observed when V. cholerae and V. vulni¢cus were induced into the VBNC state at a low temperature and subsequent resuscitation was performed by temperature upshift [7,16]. The ability to regain the culturability of nonculturable cells might have decreased during periods after entry into the VBNC state.…”
Section: Discussionsupporting
confidence: 59%
“…After 10 days in the nonculturable state (22 days after commencement of the experiment), no cells were recovered after resuscitation on the amended plates (data not shown). A similar phenomenon has been observed when V. cholerae and V. vulni¢cus were induced into the VBNC state at a low temperature and subsequent resuscitation was performed by temperature upshift [7,16]. The ability to regain the culturability of nonculturable cells might have decreased during periods after entry into the VBNC state.…”
Section: Discussionsupporting
confidence: 59%
“…Since culture methods are unable to recover nonculturable cells, we also evaluated the ability of the immunoassay to detect dormant biotype 2 cells. The dormancy was induced in saline-water microcosms maintained at 4ЊC as previously described (9).…”
Section: Continued On Following Pagementioning
confidence: 99%
“…In fact, the two biotypes share several virulence determinants, such as exotoxin production and expression of capsule and siderophore-dependent iron acquisition mechanisms (3,5,12,14), and the exotoxins produced by the two biotypes are equally lethal for eels and mice (7). Encapsulated cells of biotype 2, like biotype 1 cells, can be transmitted to new hosts through brackish water (4), where they survive as freeliving microorganisms for at least a month (9). The two biotypes also share many genotypic and phenotypic traits, including cytotoxin-hemolysin genes, immunologically related outer membrane proteins, soluble intracellular proteins, etc.…”
mentioning
confidence: 99%
“…Our investigations have revealed that biotypes 1 and 2 of V. vulnificus exhibit a high level of phenotypic homology, sharing many biochemical traits, immunologically related outer membrane proteins (OMPs), the expression of several virulence factors, and virulence for mice (2,5,9,(13)(14)(15)(16). Further, we have demonstrated the survival of the eel pathogen in seawater as a free-living microorganism, as well as its water-borne transmissibility (3,11). However, the two biotypes still can be differentiated based on biochemical and serological properties, as well as by eel pathogenicity (16).…”
mentioning
confidence: 90%